Toughened and strengthened silicon carbide ceramics by adding graphene-based fillers. (1st March 2016) - Belmonte, Manuel; Nistal, Andrés; Boutbien, Pierre; Román-Manso, Benito; Osendi, María I.; Miranzo, Pilar
Abstract: Graphene nanoplatelets and reduced graphene oxide (rGO) were selected as fillers to develop reinforced silicon carbide (SiC)/graphene composites. The mechanical properties of the materials were investigated as a function of the type of graphene source and graphene content. Composites containing just 5 vol.% of rGOs exhibited an outstanding mechanical performance, increasing both the fracture toughness by ~ 162%, with a maximum value of 8.3 MPa · m 1/2, and the strength by ~ 60% (600 MPa) when compared to monolithic SiC. The preferential alignment of the graphene fillers, their dimensions, and the graphene-SiC mechanical interlock are key factors to promote crack shielding mechanisms. Graphical abstract: